2011
DOI: 10.1007/s11481-011-9312-5
|View full text |Cite
|
Sign up to set email alerts
|

Non-Steroidal Anti-Inflammatory Drugs and Cognitive Function: Are Prostaglandins at the Heart of Cognitive Impairment in Dementia and Delirium ?

Abstract: Studies of non-steroidal anti-inflammatory drugs (NSAIDs) in rheumatoid arthritis imply that inflammation is important in the development of Alzheimer’s disease (AD). However, these drugs have not alleviated the symptoms of AD in those who have already developed dementia. This suggests that the primary mediator targeted by these drugs, PGE2, is not actively suppressing memory function in AD. Amyloid-β oligomers appear to be important for the mild cognitive changes seen in AD transgenic mice, yet amyloid immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 149 publications
0
34
0
Order By: Relevance
“…While subacute ibuprofen treatment improves memory and synaptic plasticity in amyloid AD mouse models (Kotilinek, et al, 2008, Van Dam, et al, 2010), to our knowledge, this is a first report showing the protective effects of ibuprofen against cognitive decline in aged wild-type mice. Ibuprofen is one of the classical types of NSAIDs, which suppresses the prostaglandin biogenesis from arachidonic acid by inhibiting functions of cyclooxygenase (COX)-1 and COX-2 (Cunningham and Skelly, 2012). Chronic inflammation occurs in the hippocampus of aged rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While subacute ibuprofen treatment improves memory and synaptic plasticity in amyloid AD mouse models (Kotilinek, et al, 2008, Van Dam, et al, 2010), to our knowledge, this is a first report showing the protective effects of ibuprofen against cognitive decline in aged wild-type mice. Ibuprofen is one of the classical types of NSAIDs, which suppresses the prostaglandin biogenesis from arachidonic acid by inhibiting functions of cyclooxygenase (COX)-1 and COX-2 (Cunningham and Skelly, 2012). Chronic inflammation occurs in the hippocampus of aged rats.…”
Section: Discussionmentioning
confidence: 99%
“…Sulindac treatment also attenuated an age-related decrease in the NR1 and NR2B NMDA receptor subunits, which are associated with PSD-95 at the post-synaptic cleft (Mesches, et al, 2004). Since prostaglandins trigger diverse inflammatory cascades in the brain (Cunningham and Skelly, 2012), subacute ibuprofen treatment may also rescue aging-related cognitive declines by preventing the prostaglandin-mediated neuroinflammation via COX-2 inhibition. However, COX-2 is controversially required to mediate the consolidation of hippocampal-dependent memory in rats (Teather, et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Interventions based on inhibition of inflammation in AD patients have in most cases not been successful [27]. In addition, long-term use of NSAIDs may induce gastrointestinal and cardiovascular side effects [28]. Therefore, there is call for a novel strategy, not based on classical anti-inflammatory treatment, and therapeutic strategies based on resolving the inflammatory state in AD are therefore of interest.…”
Section: Introductionmentioning
confidence: 99%
“…7,8,27,28 On the other hand, the antiinflammatory effects were effective for the prevention of cognitive impairment even in chronic situations. 29 In the current study, NSAIDs were identified as a predictive factor for agitation severity of delirium in terminally ill cancer patients. The reason might be because NSAIDs are usually used in patients with uncontrollable pain 30 and fever.…”
Section: Discussionmentioning
confidence: 80%